2013
DOI: 10.1073/pnas.1318309110
|View full text |Cite
|
Sign up to set email alerts
|

C1q induction and global complement pathway activation do not contribute to ALS toxicity in mutant SOD1 mice

Abstract: Accumulating evidence from mice expressing ALS-causing mutations in superoxide dismutase (SOD1) has implicated pathological immune responses in motor neuron degeneration. This includes microglial activation, lymphocyte infiltration, and the induction of C1q, the initiating component of the classic complement system that is the protein-based arm of the innate immune response, in motor neurons of multiple ALS mouse models expressing dismutase active or inactive SOD1 mutants. Robust induction early in disease cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 60 publications
(116 reference statements)
3
68
0
Order By: Relevance
“…Complement factors are mostly synthesized in the liver, but in mSOD1 transgenic animal models, complement factor C1q transcription was noted to be upregulated in motor neurons [102]. However, the role of the complement pathway still remains controversial [103][104][105][106]. The role of peripheral monocytes in ALS is also controversial.…”
Section: Additional Peripheral Immune Contributionsmentioning
confidence: 99%
“…Complement factors are mostly synthesized in the liver, but in mSOD1 transgenic animal models, complement factor C1q transcription was noted to be upregulated in motor neurons [102]. However, the role of the complement pathway still remains controversial [103][104][105][106]. The role of peripheral monocytes in ALS is also controversial.…”
Section: Additional Peripheral Immune Contributionsmentioning
confidence: 99%
“…By contrast to the above studies, which indicates a role for the classical complement pathway in the progression of pathology of the hSOD1 transgenic mouse, recent studies have demonstrated that when hSOD1 transgenic mice were bred onto a background deficient in complement C1q, C3 and C4, there was no difference in the onset of motor symptoms and survival when compared to hSOD1 transgenic mice (Chiu et al, 2009, Lobsiger et al, 2013. These studies indicate that blocking upstream complement activation pathways does not alter the disease course in hSOD1 transgenic mice.…”
Section: Clinical Evidence Of Complement Involvement In Alsmentioning
confidence: 76%
“…Intriguingly, recent studies have shown deletion of C1q, C3 and C4 in hSOD1 transgenic mouse models did not show any beneficial effects on the disease progression of ALS (Chiu et al, 2009, Lobsiger et al, 2013.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations